Evaluation of different desensitizing agents on dentinal tubule occlusion: A scanning electron microscope study - Saleeta Mushtaq; Rajan Gupta; Parveen Dahiya; Mukesh Kumar; Vrishti Bansal; Sunita R Melwani (Wolters Kluwer Medknow Publications, 2019)
Background: Dentinal hypersensitivity occurs on exposed dentin and depends on the patency of dentinal tubules. The purpose of this study was to evaluate different desensitizing agents on dentinal tubule occlusion by scanning electron microscopy. Materials and Methods: Thirty teeth were collected from extracted sound maxillary premolars. Samples were sectioned mesiodistally to obtain 30 buccal and 30 lingual surfaces, and enamel was removed in order to simulate hypersensitive dentin. Specimens were randomly divided into four groups. Group 1: 10 samples were coated with Gluma desensitizer, Group 2: 10 samples were coated with VivaSens, Group 3: 10 samples were coated with MS Coat, Group 4: 10 samples each of the contralateral parts of samples were coated with Gluma desensitizer, VivaSens, and MS Coat on which no desensitizing agent was applied, which acted as the controls. All the specimens were examined under SEM, and photomicrographs were evaluated to assess the opening of dentinal tubules in the controls and occlusion of dentinal tubules in their contralateral parts coated with the desensitizing agents. Results: Statistically significant amount of tubules got occluded after the application of MS Coat desensitizer as compared to tubules that got occluded after the application of VivaSens desensitizer and Gluma desensitizer. Conclusion: MS Coat showed better results in the closure of the dentinal tubules, followed by VivaSens and then Gluma desensitizer.